Tsetse feeding habits and tsetse challenge at sites of the African Trypanotolerant Livestock Network - Leak, S.G.A.; Colardelle, C.; Coulibaly, L.; D'Ieteren, G.D.M.; Dumont, P.; Feron, A.; Hecker, P.; Jeannin, P.; Maloo, S.H.; Minengu, M.; Minja, S.; Mulatu, W.; et al. (OAU/STRC, 1991)
Reports the feeding preferences of Glossina species at sites of the African Trypanotolerant Livestock Network. Estimates tsetse challenge and relates the results with trypanosome prevalence in cattle. Examines the relationship between tsetse challenge using linear regression analysis. Also examines the difference between the slopes of the regression lines obtained for trypanotolerant and susceptible cattle using a 't-test'.